Ақпараттық-коммуникациялық технологияларды пайдалану оқушылардың өзін-өзі бағалау тиімділігін арттыру нышаны ретінде - Жапарова, Г.А. (My University, 2016)
The following article shows the ideas of level modular programs used in the Nazarbayev Intellectual schools that develop critical thinking skills, self-development and self-evaluation. The article shows the learning process that is directed by teacher, the teacher also advises and monitors, and students independently plan, perform and self-assess. Moreover, the article analyzes the effectiveness of the module "Information and communication technologies in teaching and learning," demonstrating the results of actionresearch in traditional assessment, in the framework of criteria-based assessment.
Keywords: ICT; self-assessment; criteria-based assessment; action Research; action learning